Alternative protein sources in the nutrition of farm animals - Mézes, Miklós (Acta Agraria Debreceniensis, 2018)
Protein requirement and its demand of farm animals became one of the critical problems in nutrition on a global scale. Protein requirement has been an explicit demand for a long period with soybean meal and animal protein, but recently there are some limitations in relation to their use and the availability of the high quality fishmeal decreases constantly. For this reason there is increased demand for finding new protein sources which could be the alternatives of soybean meal and fishmeal. Alternative protein sources can be divided into seven categories, according to their origin. In different countries, their use depends on the availability in large quantity and at reasonable price. There is a long tradition of using legume seeds, as alternatives of soybean. Most of them contain some anti-nutritive compounds, but it can be reduced with systematic selection. Oilseed meals are also generally use in poultry and pig nutrition, but those crude protein content varied, depending on the oil extraction technology. Green fodder and leaf protein was also proposed as alternative protein sources, but their use is limited, in particular because of the market price. The amount of bioethanol and starch industry by-products increases gradually in recent years, therefore those became alternatives of soybean meal, or in much less extend, fishmeal. However, amino acid composition of such by-products are far from optimal for poultry and pig; therefore, in the case of their use amino acid supplementation is necessary. Several novel protein sources are proposed in the last decade, such as algae or insect proteins. Recently, their availability and use is limited, but in the near future those would be alternative protein sources in monogastric animal nutrition.